Analisis Karakter Morfologi Untuk Menentukan Hubungan Kekerabatan Jenis Ikan Baronang (Siganus spp.) di Desa Labean Kabupaten Donggala - Burhanuddin, Alga Patricia; Budiarsa, I Made; Kundera, I Nengah; Ramadhan, Achmad; Jayanti, Zulaikhah Dwi; Trianto, Manap (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This research aims to describe the kinship relationship of baronang fish species, based on morphological character analysis. The approach used is descriptive explorative. Research samples were obtained from the sea waters of Labean Village, Donggala Regency using purposive sampling techniques. The obtained baronang fish were then identified and measured based on 21 morphometric characters, 5 meristic characters, and 4 qualitative characters in each of the six species found. Data is processed using Microsoft Excel then analyzed using cluster analysis on MVSP (Multivariate Statistical Package) software. The similarity index uses the Simple Matching Coefficient method, the reconstruction of the dendogram using the UPGMA algorithm. The results of this research found six species of baronang fish, namely: Siganus canaliculatus, Siganus doliatus, Siganus vulpinus, Siganus vermiculatus, Siganus guttatus, and Siganus puellus. The kinship relationship between six types of baronang fish is formed into five clusters with various kinship categories, namely very close, close, and not close. The first cluster shows a very close kinship occupied by Siganus canaliculatus with Siganus doliatus with a similarity index of 0.93%. Meanwhile, the fifth cluster that shows not close kinship is the grouping between fish species on Node 4 with fish species on Node 3 with a similarity index of 0.43%. The results of this research, are expected to be the basis for further research related to kinship or the development of baronang fish species in Labean Village, Donggala Regency.